The Spatial Concentration of Peacekeeping Personnel and Public Health During Intrastate Conflicts. Issue 3 (27th May 2018) - Reeder, Bryce W.
ABSTRACT: The literature on the effectiveness of peacekeeping has been focused almost exclusively on conflict mitigation. This article expands the scope of this literature by developing a theory that explains how the presence of peacekeeping forces improves population health during periods of intrastate conflict. The argument is put forth that because civil conflict violence clusters geographically it undermines the herd immunity critical-mass threshold. This, in turn, leads to increased infection rates and a tragic surge in preventable deaths. Peacekeepers, because they target conflict 'hot spots' locally, put an end to this cycle and assist in the restoration herd immunity. Using a unique measure of peacekeeping that accounts for the area of the conflict zone, the empirical models uncover a positive relationship between peacekeeping forces and immunization rates, as vaccination rates increase when peacekeepers are deployed into violent conflicts. These findings suggest that peacekeeping missions have the potential to reduce the public health costs imposed by internal conflicts.